Embedded media processing - Katz,David J. (Elsevier/Newnes, 2006)
Both the experienced system designer and the student will find value in this comprehensive work. More practical than a theoretical text, it's what an expert engineer would tell a peer embarking on the journey of embedded media processing. Notably reader-friendly for a subject this complex, this book should give anyone access to multimedia design techniques including memory partitioning, data movement, and power considerations